PENGARUH SUPERVISI, MOTIVASI KERJA DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU KELAS DI KECAMATAN PEUSANGAN KABUPATEN BIREUEN - Raimah, Raimah; Kamaruddin, Kamaruddin (LPPM-UNIKI, 2022)
The purpose of this study was to measure and analyze: influence of supervision, work motivation and principal's leadership on the teaching performance of classroom teachers in Peusangan District, Bireuen Regency. The study was conducted on 160 classroom teachers in Peusangan District, Bireuen Regency with a quantitative research approach with the instrument using a questionnaire. And the analysis technique uses path analysis. The results showed that 1) There was a positive and significant effect of Supervision of School Supervisors on the performance of elementary school teachers in Peusangan District, Bireuen Regency, which was 32.92%. 2). The results of the hypothesis test prove that the influence of the achievement motivation factor of classroom teachers in Peusangan District, Bireuen Regency has a significant effect on teacher performance, which is 17.26%. 3) And it is proven that the Principal's Leadership has a significant effect on the performance of elementary school teachers in Peusangan District, Bireuen Regency which is calculated from this study by 8.44%. 4). Simultaneously, the results showed that the variables of School Supervisor Supervision, Teacher Achievement Motivation and Principal Leadership had a significant effect on teacher performance. The contribution of these three factors is 58.6%.